Association between Interleukin-6 and Anemia of chronic Disease (ACD) in Patients with Systemic lupus Erythematosus - Alnaaly, Abbas Sabbar Dahkil (Al-Qadisiyah Journal of Pure Science, 2017)
This study was performed to determine the concentrations of serum interleukin-6 (IL-6) and its correlation with iron status: serum iron, serum transferrin and serum ferritin in patients with systemic lupus erythematosus (SLE). We obtained serum samples from 50 patients with SLE who had visited Al-Diwanyia Teaching Hospital and 20 age- and sex-matched healthy controls, and we assessed the clinical parameters of disease, including seropositivity test for systemic lupus erythematosus (SLE), erythrocyte sedimentation rate (ESR). Serum levels of iron and total iron binding capacity (TIBC) were measured spectrophotometrically, and transferrin concentration were calculated mathematically. Serum concentrations of interleukin-6 (IL-6) and ferritin were measured using an enzyme-linked im-munosorbent assay (ELISA). Serum concentration of interleukin-6 (IL-6) was significantly elevated (P> 0.0001) in patients with SLE compared to those of healthy controls. Serum concentrations of iron, total iron binding capacity (TIBC), and transferrin concentration were significantly decreased in patients with SLE compared to those of healthy controls. While serum level of ferritin was significantly elevated (P> 0.0001) in patients with SLE compared to those of healthy controls. We concluded that the serum concentrations of iron and transferrin were sig-nificantly decreased in SLE patients. Most importantly, these changes correlated with the inflammatory state of the patients (significant elevation of IL-6, ferritin and ESR) and anemia of chronic disease. Taken together, altered iron handling, inflammation and anemia of chronic disease constitute an ominous triad in SLE.